Tradisi Barzanji pada Etnis Bugis di Desa Tinete Kecamatan Aere Kabupaten Kolaka Timur Sulawesi Tenggara - Nurtikawati Nurtikawati; Sukmawati B; La Niampe (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2022)
The Barzanji tradition is a custom or ritual that must be carried out at every celebration so that it still survives today. This study aims to understand the pattern of inheritance and examine the meaning contained in the tradition. This type of research is a qualitative research whose data is obtained from the results of observations, interviews, and documentation and uses the theory of semiotics. The results of this study indicate that the process of implementing the Barzanji tradition consists of several stages, namely preparation, implementation and the final stage. The Barzanji tradition is understood by the Bugis people as a good tradition to maintain its existence. This is because in its implementation it provides benefits for their lives and as an expression of gratitude, grounding shalawat, and as a forum for Islam.